Nominations of the russian-ukrainian war in multi-style discourse - BRAILKO, Iuliia; KYSLA, Nataliia (Ukrainian linguistics, 2024)
Background. The article identifies the nominations of the Russian-Ukrainian war in the texts of different styles; it analyzes the functional specifics of the concepts “war,” “armed aggression,” “full-scale invasion,” “conflict,” “ATO,” “JFO,” “Russian-Ukrainian war,” etc. The armed aggression of the Russian Federation against Ukraine has been going on for more than a decade, and its full-scale period is more than three years, but Ukrainian speakers have not yet developed a suitable militonym. Both in scientific sources and in the mass media, there are still ongoing discussions about the appropriateness of the concepts “war,” “armed aggression,” “full-scale invasion,” “conflict,” etc. to mark this event. Methods. A complex of the following methods has been used to study the nominations of the modern Russian-Ukrainian war: an index of such names has created using the selection method; the linguistic stylistic method has made it possible to trace the peculiarities of the functioning of militonyms in texts of different styles; component analysis has enabled the identification of semantic components of these names; contextual and discursive analysis have allowed us to identify their pragmatics; thanks to the descriptive method the results of the research are highlighted. Results. It has been found that the concept “anti-terrorist operation” was used in Ukrainian legislation until February 24, 2022. The same concept was the main lexical marker of current military events in Ukraine in texts of various styles from 2014‒2018. After 2018, the concept “JFO” became fixed in the media discourse, and the abbreviation “ATO” continued to be mostly used in colloquial, journalistic, and artistic discourse. The factonym “armed aggression of the Russian Federation [against Ukraine]” has gradually entered the legal circulation, and later also the scientific and journalistic discourse. Despite the wide palette of names of modern military events, the lexeme “war” dominates the colloquial and artistic discourse. Conclusions. The same events, phenomena, processes can be called differently. And such nominations can be an informational weapon of Ukrainians in the war against the Russian aggressor, as well as a weapon of Russian propaganda. Undoubtedly, it is a matter of time to select and establish in the Ukrainian discourse the militonym for the designation of modern military actions. We will make an assumption that it will be multi-component, and in view of the conducted research, we will note that the lexeme “war” should be the key one in its structure, as it is the most used by modern speakers to mark the armed aggression of the Russian Federation against Ukraine from 2014 to the present day. Information about the author: Iuliia BRAILKO – PhD (Philol.), Assoс. Prof., Poltava Branch of National Scientific Center “Hon. Prof. M. S. Bokarius Forensic Science Institute” (Ukraine) E-mail: brailko.iuliia@nncise.org.ua Nataliia KYSLA – PhD (Philol.), Leading Researcher, Poltava Branch of National Scientific Center “Hon. Prof. M. S. Bokarius Forensic Science Institute” (Ukraine) E-mail: kysla.nataliia@nncise.org.ua __________ REFERENCES • Conflict. https://sum20ua.com/?page=1386&searchWord=konflikt&wordid=43842 [in Ukrainian]. • Horodenska, K. (2015). Atoshnyk or atovets? The Word Culture, 83, 127 [in Ukrainian]. http://dspace.nbuv.gov.ua/bitstream/handle/123456789/112512/23-Horodenska.pdf?sequence=1 • Melnyk, S. M., Nazarenko, O. M., & Sikorska, V. Yu. (2023). Linguistic representation of the “war” concept in modern Ukrainian media discourse. Philological education and science: transformation and modern development vectors (рр. 446–467). “Baltija Publishing” [in Ukrainian]. http://baltijapublishing.lv/omp/index.php/bp/catalog/download/297/8542/17835-1?inline=1 • Pecherskyi, A. (2022). The way the language constructs the reality of war [in Ukrainian]. https://armyinform.com.ua/2022/08/26/yak-mova-konstruyuye-realnist-vijny/ • Pylypenko, Ya. (2017). Demarction configures “military conflict”, “armed conflict” and “war”. National Technical University of Ukraine Journal. Political science. Sociology. Law, 1/2 (33/34), 143‒146 [in Ukrainian] . https://doi.org/10.20535/2308-5053.2017.1/2(33/34).152571 • Tepla, O. (2023). The concept of “war” in the linguistic and cultural aspect (based on the material of publicistic discourse). International journal of philology, 14, 3, (рр. 92–100) [in Ukrainian]. http://dx.doi.org/10.31548/philolog14(3).2023.010 • Vilchynska, (2017). Concept “War”: Peculiarities of Lingual Instantiation in Newspape. Linguistic studies, 34, 110–114 [in Ukrainian].